2001
DOI: 10.1002/1615-9861(200109)1:9<1111::aid-prot1111>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed proteins in the interaction of Xanthomonas axonopodis pv. citri with leaf extract of the host plant

Abstract: The present study reports the expression of proteins of Xanthomonas axonopodis pv. citri in response to different growth conditions. The bacterium was cultured in the basal medium MM1 and in the presence of leaf extracts from a susceptible host plant (sweet orange) as well as a resistant (ponkan) and a nonhost plant (passion fruit). The protein profiles were analyzed by two-dimensional gel electrophoresis (2-DE). Twelve differential spots (induced, up- and down-regulated and repressed) were observed in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…After 12 h growth in NYG, X. axonopodis pv. citri is close to the stationary phase (Mehta and Rosato, 2001), which could explain the expression of the transposon ISXac3 in this treatment. In X. axonopodis pv.…”
Section: Mehta and Rosato 145mentioning
confidence: 95%
See 3 more Smart Citations
“…After 12 h growth in NYG, X. axonopodis pv. citri is close to the stationary phase (Mehta and Rosato, 2001), which could explain the expression of the transposon ISXac3 in this treatment. In X. axonopodis pv.…”
Section: Mehta and Rosato 145mentioning
confidence: 95%
“…The induction time and leaf extract concentration of the culture media were previously determined by Mehta and Rosato (2001) in the analysis of the differential expression of proteins of X. axonopodis pv citri. The bacterium was also recovered from host plant leaves 6 days after inoculation.…”
Section: Rna Preparation and Cdna Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…These metabolites may play a role in the interaction of plants with biotic and abiotic environmental factors (23). Other studies that supplemented bacterial culture media with plant leaf extract or plant flavonoids have shown that compounds derived from plant can stimulate differential expression of bacterial proteins (11,15).…”
Section: Effect Of Pc Extract On the Expression Of Xylella Fastidiosamentioning
confidence: 99%